Pengembangan Electronic Government Dalam Peningkatan Potensi Sektor Pariwisata (Studi pada Dinas Pariwisata dan Kebudayaan Kota Batu) - Ismianto, Wahyu Septian (Jurnal Administrasi Publik, 2014)
Abstract: The Development of Electronic Government on increasing the potential of the tourism sector (Study in Tourism and Culture Official of Batu City). Electronic Government relating to the provision of information, services or products are prepared electronically by the government, is not limited to place and time, offering more value for participation in all walks of life. The Development of Electronic Government is closely related to the use of information technology as a highly effective means of promotion. At the level of government we know the term Electronic Government which is becoming a trend nowadays, the global technology developments that hit all aspects of life and bring a lot of revolutionary changes. On tourism to be one of their field of local government to improve the tourism potential in the region by making use of electronic government. So the implementation of electronic government to provide direction, guidance and legal foundations in the development, implementation and developments of management information systems at the local level and its entire staff. This research is focused to find and describe how the development of electronic government in the improvement of the tourism sector and the factors that influence the development of electronic government in improving the tourism sector. Keywords: electronic government, tourism   Abstrak: Pengembangan Electronic Government dalam Peningkatan Potensi Sektor Pariwisata (Studi pada Dinas Pariwisata dan Kebudayaan Kota Batu). Electronic Government berhubungan dengan penyediaan informasi, layanan atau produk yang disiapkan secara elektronik oleh pemerintah, tidak terbatas tempat dan waktu, menawarkan nilai lebih untuk partisipasi pada semua kalangan. Pengembangan electronic government memang erat sekali kaitannya dengan penggunaan teknologi informasi yang sebagai sarana promosi yang sangat efektif. Pada tataran pemerintahan kita mengenal istilah electronic government yang  membuat terkenal hingga sekarang, perkembangan teknologi secara menyeluruh yang terjadi pada semua segi kehidupan dan akan memengaruhi  perubahan yang semakin besar. Dalam pariwisata menjadi suatu fokus satu-satunya pembenahan pemerintah daerah untuk memajukan daya tarik pariwisata di daerah dengan menggunakan electronic government. Agar pelaksanaan electronic government dapat  menentukan tujuan, dan aturan hukum yang berlaku dalam  pembangunan, pelaksanaan dan peningkatan sistem informasi manajemen di lingkup pemerintah daerah dan semua elemennya. Penelitian ini diarahkan untuk mengetahui dan menggambarkan bagaimana pengembangan electronic government dalam meningkatkan sektor pariwisata dan faktor apa sajakah yang menjadi pengaruh pengembangan electronic government dalam peningkatan sektor pariwisata.   Kata kunci: electronic government, pariwisata